The nematode worm Caenorhabditis elegans as an animal experiment replacement for assessing the virulence of different Salmonella enterica strains - Burkhardt, Wiebke; Salzinger, Carina; Fischer, Jennie; Malorny, Burkhard; Fischer, Matthias; Szabo, Istvan (Frontiers in Microbiology, 2023)
Caenorhabditis (C.) elegans has become a popular toxicological and biological test organism in the last two decades. Furthermore, the role of C. elegans as an alternative for replacing or reducing animal experiments is continuously discussed and investigated. In the current study, we have investigated the question of whether C. elegans survival assays can be helpful in determining differences in the virulence of Salmonella enterica strains and to what extent C. elegans assays could replace animal experiments for this purpose. We have focused on three currently discussed examples: we compared the longevity of C. elegans when fed (i) with S. enterica serovar Enteritidis vaccination or wild type strains, (ii) with lipopolysaccharide (LPS) deficient rough or LPS forming smooth S. enterica serovar Enteritidis, and (iii) with an S. enterica subsp. diarizonae strain in the presence or absence of the typical pSASd plasmid encoding a bundle of putative virulence factors. We show that the C. elegans survival assay was able to indicate differences in the longevity of C. elegans when fed with the compared strain pairs to a certain extent. In fact, putatively higher virulent S. enterica strains reduced the lifespan of C. elegans to a greater extent than putatively less virulent strains. The C. elegans survival assay is an effective and relatively easy method for classifying the virulence of different bacterial isolates in vivo, but it has some limitations. The assay cannot replace animal experiments designed for determining differences in the virulence of Salmonella enterica strains. Rather, we recommend using the described method as a pre-screening for bacterial strains of interest to select the most promising candidates for further animal experiments. The C. elegans assay does have the potential to reduce the number of animal experiments. Further development of the C. elegans assay in conjunction with e.g. omics technologies such as transcriptomics could refine results in relation to the estimation of the virulent potential of test organisms.